2010
DOI: 10.1016/j.clim.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of AIRE polymorphisms in melanoma

Abstract: Polymorphisms of AIRE, a transcription factor that up-regulates intrathymic expression of tissue-specific antigens including melanoma-associated antigens (MAAs), may variably affect the selection of MAAs-specific thymocytes, generating T-cell repertoires protecting or predisposing individuals to melanoma. We found that AIRE single nucleotide polymorphisms (SNPs) rs1055311, rs1800520 and rs1800522 were significantly more frequent in healthy subjects than in melanoma patients, independently from sex, age and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
1
16
0
2
Order By: Relevance
“…Those T regulators are thought to be major barrier impeding antitumor immune response (42). In melanoma, polymorphisms in AIRE may variably affect the selection of melanoma-associated antigen-specific thymocytes, generating T-cell repertoires protecting or predisposing individuals to cancer (43). CARD4/NOD1 is a member of the NOD receptor family that plays a major role in innate and adaptive immunities.…”
Section: Discussionmentioning
confidence: 99%
“…Those T regulators are thought to be major barrier impeding antitumor immune response (42). In melanoma, polymorphisms in AIRE may variably affect the selection of melanoma-associated antigen-specific thymocytes, generating T-cell repertoires protecting or predisposing individuals to cancer (43). CARD4/NOD1 is a member of the NOD receptor family that plays a major role in innate and adaptive immunities.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are likely to translate to patients, since human mTECs express a large number of known melanoma antigens 69 . Furthermore, case-control studies have associated melanoma protection with Aire polymorphisms that decrease Aire expression 70 .…”
Section: Other Aire Functions In Mtecsmentioning
confidence: 99%
“…All 79 patients included in this study were randomized to the ipilimumab-alone arm. The rs1055311 TT polymorphism, which has previously been associated with protection from melanoma development (12), was present in 6 of 79 patients (7.6%). The presence of the rs1055311 TT polymorphism was associated with increased probability of progression-free survival (Fisher's exact test, P = 0.036; Figure 1C) and trended toward increased probability of overall survival, although this did not reach statistical significance (log rank P = 0.13; Figure 1D).…”
Section: Aire Deficiency Enhances Antimelanoma Effects Of Ctla-4 Blocmentioning
confidence: 99%
“…However, only 10%-20% of patients respond to treatment (2,20,21), and the factors that determine response are unclear. Multiple Aire polymorphisms, including one that may negatively affect mRNA Aire stability (12), have been associated with protection from melanoma development. This suggested that Aire polymorphisms that disrupt Aire function may enhance antimelanoma immunity in humans.…”
Section: Aire Deficiency Enhances Antimelanoma Effects Of Ctla-4 Blocmentioning
confidence: 99%
See 1 more Smart Citation